Increase in steviol glycosides production from Stevia rebaudiana Bertoni under organo-mineral fertilization (2020)
The production of steviol glycosides, the active substance of Stevia rebaudiana plants, are of great medicinal and nutraceutical importance worldwide. Its production can be affected by diverse agronomic factors, including fertilization. The aim of this work was to assess the effect of organo-mineral fertilization (composted poultry manure mixed with inorganic fertilizer) on steviol glycosides and biomass production from two commercial crops of Stevia cv. Morita II under greenhouse conditions at two different locations (at 2569 and 1487 m.a.s.l). The effect was evaluated after 60 days, assessing steviol glycosides production (stevioside, rebaudioside A and C), biomass production and macro and micronutrients levels in leaves (nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, zinc, iron, manganese and boron). The results showed that OM fertilizer (compost from poultry manure (hen) with inorganic salts) had an influence on biomass and total sglys production at Heliconia (1487 m.a.s.l.) and Santa Elena (2569 m.a.s.l.), performing better than or similar to mineral fertilizer. The correlation analysis revealed that nutrients as nitrogen, calcium, magnesium and sulfur had a significant correlation with steviol glycoside production. Likewise, these nutrients increased with organo-mineral fertilization. Thus, this work suggests that the application of organo-mineral fertilizer is recommended for increasing the productivity of S. rebaudiana in terms of biomass and steviol glycosides production under greenhouse conditions in Colombia. Efficient organic material uses in crop production, decrease dependence on the use of mineral fertilizers. © 2020 Elsevier B.V.